Analysis of Q Fever Incidence in the Russian Federation Between 1957 and 2019 - S. N. Shpynov; N. V. Rudakov; S. Yu. Zelikman (Проблемы особо опасных инфекций, 2021)
Objective of the study was to analyze the long-term incidence of Q fever in the Russian Federation, to recommend approaches to improve epizootiological and epidemiological surveillance of this infection, taking into account the current state of laboratory diagnostics and monitoring of foci.Materials and methods. A retrospective epidemiological analysis of the Q fever incidence using the data contained in Form No 2 of the state statistical report «Information on infectious and parasitic diseases» was conducted in the Russian Federation for the period of 1957– 2019, by the Federal Districts (FD) and administrative territories, and based on the results of the research of the Reference Center for Rickettsioses of the Omsk Research Institute of Natural Focal Infections.Results and discussion. Between 1957 and 2019, 13 836 cases of Q fever were officially registered in the Russian Federation. The maximum value of the morbidity rate per 100 thousand of the population was registered in 1957 (1.0 0/0000), the minimum one – in 2008 (0.01 0/0000). From 1997 to 2019, out of 2672 registered in 24 entities of the Russian Federation cases of Q fever, 2224 (83.20 %) occurred in the Southern FD with 2106 (78.8 %) cases in the Astrakhan Region. In the Stavropol Territory of the North Caucasus FD, 173 (6.47 %) cases of the disease were detected. 112 (4.19 %) cases were registered in the Central FD, with the maximum number in the Voronezh Region (82). In the Volga FD, 81 (3.03 %) cases were identified, 54 of which in the Ulyanovsk Region. 42 (1.61 %) cases of the disease were registered in the North-Western FD, 33 – in the Leningrad Region and St. Petersburg. In the Siberian FD, 39 (1.46 %) cases of Q fever were reported, 24 were diagnosed in the Novosibirsk Region. In the Ural FD, 1 (0.04 %) case of infection was detected. In the Far Eastern FD, there is no registration of Q fever. Presented are medical products for Q fever diagnostics authorized in Russia. Sanitation of the foci among farm animals should be carried out in accordance with the current sanitary-epidemiological and veterinary-sanitary rules.